ANALISIS WHITE LIES ORANGTUA PADA ANAK DISABILITAS DI SLB ABCD SEJAHTERA BOGOR - Safitri, Rika Nurismah; Samatan, Nuriyati (Jurnal Common, 2021)
Parents have big role to the growth and development of children. Not all children born with perfect condition, there is children born with limits called disability. Sometimes, parents worried to their children when they do something, especially to children with disability. The parents have solution to reduce their sense of worry by using white lies when they communicate with their children. The purpose of this research is to find out the reasons why parents use white lies and to know the implementations of white lies that used by parents to their children. The theory used in this research is dissonance cognitive theory. The method is using qualitative method, descriptive approach, and paradigm of constructive. Data collected by interview and observation. Researcher conducted the research in SLB ABCD Sejahtera Bogor and there is five informants. The results showed that the parents have uncomfortable sense when children do something, so to reduce the uncomfortable sense parents used white lies. The results of this research is appropriate with assumption of cognitive dissonance theory.